The Generational Differences in Growth-Friendly Treatment Utilization for Early-Onset Scoliosis: Original Research - Jamnik, Adam A.; Monroig-Rivera, Carlos; Fitzgerald, Ryan; Sukkarieh, Hamdi; Sawyer, Jeffrey; El-Hawary, Ron; Murphy, Robert; Hardee, Maris; Anari, Jason; Johnson, Megan; et al. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: The development of new growth-friendly techniques for treating early onset scoliosis (EOS) has resulted in a rapidly changing landscape of available treatment strategies. There is no literature revealing how a surgeon’s years in practice (YIP) is related to the EOS techniques they learned in fellowship and how their YIP influences their decision making in selecting EOS constructs. Methods: A 25-question survey was electronically delivered to 144 surgeons who treat EOS, and 87 (60%) responded. Surgeons were divided into two groups: a younger group (YG) with 0-10 YIP and an older group (OG) with ＞10 YIP. Growth-friendly techniques queried included serial casting, traditional growing rods (TGR), Vertical Expandable Prosthetic Titanium Rib (VEPTR), non-VEPTR rib constructs, Magnetically Controlled Growing Rods (MCGR), and SHILLA. A Chi-square analysis was used to determine differences between the YIP groups with regards to which techniques surgeons learned in fellowship and which techniques they use in practice. Results: One-hundred percent (38/38) of the YG surgeons were fellowship trained, vs 87.8% (43/49) of the OG surgeons. More YG vs OG surgeons received fellowship training in serial casting (84.2% vs 38.8%, p<0.001), TGR (94.7% vs 63.3%, p<0.001), VEPTR (65.8% vs 28.6, p<0.001), non-VEPTR rib constructs (55.3% vs 16.3%, p<0.001), and MCGR (47.4% vs 2%, p<0.001). OG surgeons were more likely to use TGR in the last 3 years, with 26% of YG vs 6% of OG surgeons never utilizing TGR, and 5% of YG vs 31% of OG surgeons performing TGR cases > 10 times (p=.004). Regarding treatment preferences, more YG surgeons (84.2% vs 39.6%, p<0.001) preferred to delay intervention until final fusion, rather than use any growth-friendly techniques. Furthermore, YG surgeons see a limited need for growth-friendly constructs other than MCGR. Conclusions: YG surgeons were more likely to learn growth-friendly techniques in fellowship than OG surgeons, though in their practices the groups use growth-friendly techniques at similar rates. Compared to OG surgeons, YG surgeons prefer performing definitive fusions over utilizing any growth-friendly surgical techniques.